Structure of the N=50 As, Ge, Ga nuclei - Sahin, E.; de Angelis, G.; Duchene, G.; Faul, T.; Gadea, A.; Lisetskiy, A. F.; Ackermann, D.; Algora, A.; Aydin, S.; Azaiez, F.; Bazzacco, D.; Benzoni, G.; et al. (ELSEVIER SCIENCE BV, 2012)
The level structures of the N = 50 As-83, Ge-82, and Ga-81 isotones have been investigated by means of multi-nucleon transfer reactions. A first experiment was performed with the CLARA PRISMA setup to identify these nuclei. A second experiment was carried out with the GASP array in order to deduce the gamma-ray coincidence information. The results obtained on the high-spin states of such nuclei are used to test the stability of the N = 50 shell closure in the region of Ni-78 (Z = 28). The comparison of the experimental level schemes with the shell-model calculations yields an N = 50 energy gap value of 4.7(3) MeV at Z = 28. This value, in a good agreement with the prediction of the finite-range liquid-drop model as well as with the recent large-scale shell model calculations, does not support a weakening of the N = 50 shell gap down to Z = 28. (c) 2012 Elsevier B.V. All rights reserved.
WOS: 000310091000001
Keywords: NUCLEAR REACTIONS U-238(Se-82, Ga-81), (Se-82, Ge-82), (Se-82, As-83); E=515 MeV; measured E gamma; I gamma (theta); gamma gamma-coin, reaction fragments; (fragment)gamma-coin; PRISMA magnetic spectrometer; gamma after deexcitation; Ge Compton-suppressed detectors of CLARA array; thin and thick target; deduced sigma(theta); levels; J, pi calculated levels; J, pi using shell model